The Effects of Electrode Montage on the Amplitude of Wave V in the Auditory Brainstem Response to Maximum Length Sequence Stimuli - Dzulkarnain, Ahmad Aidil Arafat; Wilson, Wayne J.; Bradley, Andrew P.; Petoe, Matthew (S. Karger AG, 2008)
The use of maximum length sequence (MLS) stimuli to elicit an auditory brainstem response (ABR) has been limited, in part, by the observation that these stimuli reduce ABR wave amplitudes. This study recorded ABR waveforms from 14 normally hearing adults using MLS click stimuli (maximum stimulus rate = 250 clicks per second) at stimulus levels of 70, 60, 50, 40, 30 and 20 dB nHL, with a vertical and then an ipsilateral electrode montage. The vertical electrode montage produced significantly larger (p ! 0.05) wave V amplitudes, with no change in wave V latencies (p 1 0.05), at all stimulus levels. This result suggests a vertical electrode montage could be used to counter some of the loss in wave V amplitude observed when using MLS stimuli.